Factors That Affect Solid Waste Management in Adjumani Town Council Adjumani District. - Aluma, Franco; Amani, Innocent Justine (Student’s Journal of Health Research Africa, 2021)
Background: The study was carried out at the Adjumani town council located in the Adjumani district. The researcher sought to determine factors affecting solid waste management in Adjumani Town Council. The study objectives were to identify the types of solid waste management, the methods of solid waste management, and to identify the challenges faced by solid waste management. Methodology: The study involved descriptive cross-sectional employing qualitative data collection using methods of simple random sampling with a sample size of 10 respondents, the study population included public health workers handling solid wastes with the help of questionnaires, oral interview and observation were the major data collection tools basing on both dependent and independent study variables. The data was analyzed and presented in tables. Results: 70% were males and 30% were females. The majority of the services related to waste management were rated 60% good and 20% fair, 10% very good and 10% bad while none were got a rating of excellent. The poor roads to the final disposal site, mechanical problems with the lorry, accumulated heaps of garbage, and lack of fences were among the problems associated with transportation. Conclusion: The study thus concluded that through the capacity of government in liaison with administrators, the public health department should put more effort into continuing education to enable the staff to improve their skills at the work that is, by training, teaching, and well sensitizing all health workers and the public in the community and become aware of solid waste management and this will help to eliminate /reduce the factors affecting solid waste management in Adjumani Town Council while aiming at higher results with good performance at the workplace.